Camels, Camel Milk, and Camel Milk Product Situation in Kenya in Relation to the World - Stephen Oselu; Rebecca Ebere; Joshua M. Arimi (International Journal of Food Science)
Kenya is the leading camel milk producer globally, with an annual production volume of 1.165 MMT, followed by Somalia (0.958 MMT) and Mali (0.271 MMT). In Kenya, pastoral tribes in North-Eastern parts rear about 4.722 million camels accounting for about 80% of all camels. Camels offer locals various benefits, including transportation of goods across the deserts, meat, fur, and milk. Camel milk contains natural therapeutically and immunity-boosting properties due to the higher concentration of lactoferrin, lactoglobulins, and lysozyme than bovine milk. Camel milk has been shown to have hypoallergenicity properties compared to bovine milk. Camel and human milk are similar in nutritional composition and therapeutic properties. Camel milk is known to fight various diseases, including cancer, diabetes, autism, hypertension, and skin diseases. Despite the standing of Kenya in the world in terms of camel milk production, Kenya lags considering the camel milk products, industries, and marketing. This paper reviews recent literature on camels and camel milk production trends in Kenya in relation to the world. The review also discusses various camel milk properties (nutritional and therapeutic) as well as the camel milk sector situation in Kenya.